Pengaruh Model Discovery Learning Berbantukan Alat Peraga Sederhana Terhadap Hasil Belajar Siswa di Sekolah Menengah Pertama Negeri 10 Merangin - Suci Meiriza Ulfa KZ; Boby Syefrinando; Louisiana Muliawati (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2019)
The low student learning outcomes in Integrated Science subjects are due to several things such as learning activities that are still teacher-oriented so that students are less actively involved in the learning process. This study aims to see the effect of the Discovery Learning model using simple teaching aids on student learning outcomes in Merangin 10 State Junior High School. This type of research is Quasy Experiment with research design Posttest Only Control Group Design. The population used in this study were students of class VIII SMP Negeri 10 Merangin. The research sample was taken by using simple random sampling technique. The instrument used for learning outcomes is an objective test that has previously been tested. Based on the results of research and data processing t-test analysis at the 5% significance level, it was obtained t count> t table, namely 5.27> 2.06, meaning H_1 was accepted. Based on the Effect size test, the d_s was obtained at 1.98. These results indicate that the learning model of Discovery Learning with the help of simple teaching aids has a major influence on student learning outcomes in Integrated Science subjects at Merangin 10 State Junior High School.